Mrs Eells ’Unique Receipts’ - Potter, David (Petits Propos Culinaires, 1999)
An account of a bibliographic investigation linking a manuscript held by the Bodleian Library with the author Mrs. Mary Eales, the 18th-century author of published works on confectionery.